Effectiveness of Acuyoga (Accupresure and Yoga) Antenatal and Pregnancy Massage Against Intensity of back pain and sleep disturbance in Third Trimester Pregnant Woman in dr.Aisyatul Mukminah Sp.OG (K)'s Practice in Tulungagung - Putri Eka Sejati; Indasah Indasah; Koesnadi Koesnadi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2017)
Various physiological changes occur in the mother's body during pregnancy which can affect the occurrence of low back pain and sleep disturbance during pregnancy trimester 3. One of the non-pharmacological therapy to reduce the incidence is with antenatal acuyoga and pregnancy massage. This is because acuyoga and massage will produce more endorphins that serve to provide peace, to overcome stress during pregnancy. The purpose of research to analyze the effectiveness of antenatal acuyoga and pregnancy massage to the intensity of low back pain and sleep disturbance of pregnant women trimester III The purpose of research to analyze the effectiveness of antenatal acuyoga and pregnancy massage to the intensity of low back pain and sleep disturbance of pregnant women trimester III in dr.AisyatulMukminahSp.OG (K)'s own practice in Tulungagung. Types of analytical research associate with one group pre test model - post test design. Independent variable of antenatal acuyoga study and pregnancy massage in third trimester pregnant women, dependent variable of back pain intensity and sleep disturbance of trimester III pregnant women. The study population were All third Trimester pregnant women in dr.AisyatulMukminahSp.OG (K)'s own practice in Tulungagung. Sampling technique using simple random sampling with sample of 16 people. Data were analyzed by using Wilcoxon signed rank test, McNemar and Chi Square. The result of the research showed that there was difference of waist pain intensity of trimester III pregnant mother before and after antenatal acuyoga p = 0,005 <α (0,05). There was no difference of maternal sleep disorder of trimester III before and after performed antenatal acuyoga (p = 0,125> α (0,05) .There was difference of waist pain intensity of trimester III pregnant mother before and after pregnancy massage (p = 0,010 <α (0 , 05) .There is difference of sleep disturbance of pregnant mother of trimester III before and after done pregnancy massage (p = 0,008 <α (0,05).